Next-level negotiating. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"Whether you're negotiating a salary, a deal with a supplier, or a flexible work arrangement, you need to prepare. From knowing your ideal outcome to thinking through acceptable alternatives to considering the other person's perspective, advance planning can significantly increase your confidence, engagement in the process, and results. But it's not just practical details, numbers, and strategies-advocating for yourself, your team, and your business can feel personal, too, so you also need to manage the emotions that arise during the process. Shake off the bleak research about women and negotiation, and clarify and communicate who you are and what you need in your business and in your relationships to increase your odds of a positive outcome. Thoughtful preparation can help you enter any negotiation with curiosity, creativity, and a willingness to collaborate-all the essentials to seal a deal successfully. This book will inspire you to: set a clear outcome; explore and examine acceptable alternatives; consider your counterpart's perspective; manage your emotions; overcome stumbling blocks; discover collaborative solutions; and strike a deal that works for you"--
How Women Can Get What They Want in a Negotiation : five strategies for success / by Suzanne de Janasz and Beth Cabrera -- Understanding the Negotiation Process : do your homework and prepare for back-and-forth / a conversation with Marisa Mauro and Ashleigh Shelby Rosette -- Stop Overlooking Opportunities to Negotiate : everyday haggling can prepare you for when the stakes are high / by Suzanne de Janasz -- 3 Common Challenges Women Face in Negotiations : balance self-advocacy and community, manage difficult emotions, and overcome resistance / by Mara Olekalns, Ruchi Sinha, and Carol T. Kulik -- Look and Sound Confident During Any Presentation : six principles to practice before your next visit to the negotiating table / by Carmine Gallo -- How to Negotiate-Virtually : when there is no table / by Hal Movius -- The Most Overused Negotiating Tactic Is Threatening to Walk Away : try relationship building, exploration, creativity, or collaboration instead / by Jay A. Hewlin -- How to Bounce Back After a Failed Negotiation : don't dwell on it / by Carolyn O'Hara -- Emotion and the Art of Negotiation : don't stifle your feelings-use them to your advantage / by Alison Wood Brooks -- Using Mindfulness in Negotiation : pay attention to your body-and your triggers / by Gaëtan Pellerin -- The Science of Choking Under Pressure : lessons from elite athletes about performing in big moments / by Alyson Meister and Maude Lavanchy -- Negotiating as a Woman of Color : four common traps and how to move beyond saying yes or no / by Deepa Purushothaman, Deborah M. Kolb, Hannah Riley Bowles, and Valerie PurdieGreenaway -- Don't Ask for a Raise-Negotiate It : clarify the value you bring to your boss and to your organization / by Carol Hagh -- Women Ask for Raises as Often as Men, but Are Less Likely to Get Them : research to inspire you-and validate your experience / by Benjamin Artz, Amanda Goodall, and Andrew J. Oswald -- Even
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 25, 2023).
WorldCat record variable field(s) change: 050
Keywords: Negotiation in business; Women employees; Success in business; Psychology, Industrial; Negotiation in business; Psychology, Industrial; Success in business; Women employees